Development in a Dish—In Vitro Models of Mammalian Embryonic Development - el Azhar, Yasmine; Sonnen, Katharina F. (Frontiers in Cell and Developmental Biology, 2021)
Despite decades of research, the complex processes of embryonic development are not fully understood. The study of mammalian development poses particular challenges such as low numbers of embryos, difficulties in culturing embryos in vitro and the time to generate mutant lines. With new approaches we can now address questions that had to remain unanswered in the past. One big contribution to studying the molecular mechanisms of development are two- and three-dimensional in vitro model systems derived from pluripotent stem cells. These models, such as blastoids, gastruloids and organoids, enable high-throughput screens and straightforward gene editing for functional testing without the need to generate mutant model organisms. Furthermore, their use reduces the number of animals needed for research and allows the study of human development. Here, we outline and discuss recent advances in such in vitro model systems to investigate pre- and post-implantation development.